Toxicity Effects of Toad (Rhinella jimi Stevaux, 2002) Venom in Chicken (Gallus gallus domesticus) - Gadelha, Ivana Cristina Nunes (Hindawi Publishing Corporation, 2014)
This study aimed to evaluate the pathological changes that occur after administering different doses of R. jimi (Stevaux, 2002) parotoid glands secretion to Gallus gallus domesticus chicks. Twenty-three animals were used in this study and were divided into 5 groups that received a toad venom dose of 0, 3.0 mg/kg, 6.0 mg/kg, 10.0 mg/kg, and 25.0 mg/kg. After 48 h, the necropsy and pathological examinations were performed. No clinical signs of toxicity were observed in any group. Macroscopically, hepatomegaly, areas of liver necrosis, splenomegaly, necrotic and hemorrhagic cardiac regions, hydropericardium, dark necrotic lesions of Meckel's diverticulum, and hemorrhages in the lungs and kidneys were detected. Histopathological changes included diffuse vacuolar degeneration of hepatocytes, severe sinusoidal congestion, focal areas of hemorrhage in the parenchyma, swollen cardiac fibers, necrotic myocardial fibers, moderate to acute diffuse alveolar hemorrhage, vacuolar degeneration of the renal tubular epithelium, necrosis of renal tubules, and extensive hemorrhagic areas below the brain and cerebellar meninges. In conclusion, pathological changes of the R. jimi toxins in chicks were noted in the heart, spleen, liver, Meckel's diverticulum, lungs, and kidneys. Most of the changes were similar to those observed in humans and animals exposed to toxins from other toad species.